Wpływ wykonania szlaków operacyjnych na wartość hodowlaną jednowiekowych drzewostanów sosnowych przy różnych metodach trzebieży - Zachara, Tadeusz (Leśne Prace Badawcze, 2024)
The study was conducted on a permanent experimental plot established in 1965 in the Kozienice Forest District to investigate the effects of spacing on the growth of Scots pine. Since 1999, the plot has also been used to study the effects of thinning – using a randomized block design. In this study, seven treatments (four blocks) out of a total of nine treatments present on the plot were included. The following treatments were tested: (1) moderate selective thinning TU1 and TU2 (focusing on 500 future crop trees per hectare evenly distributed on the plot), (2) group thinning TG1 and TG2 (focusing on the same number of future crop trees not evenly distributed on the plot), (3) heavy thinning TS1 and TS2 (focusing on 350 future crop trees per hectare), and (4) control plot (K, without thinning). During the last thinning, a network of skid trails (each 17–18 m) was established in the study plot to enable the use of a harvester. The aim of the study was to evaluate the influence of the establishment of skid trails on the loss of future crop trees in different treatments. All trees removed in the period 2015–2020 (including natural mortality and mortality caused by the establishment of skid trails) were counted and their basal area calculated. ANOVA was performed to investigate the influence of thinning treatments on natural and artificial loss of trees between successive thinnings. The largest total number and basal area of trees removed was found in control plot K. The greatest loss of future crop trees was observed in the plots treated with group thinning TG1. In plots with a lower number of future crop trees (TS1), the loss was zero. In summary, the establishment of skid trails in heavily thinned Scots pine stands with wide spacing is acceptable. The skid trails should be established before the selection of future crop trees.